Estimands: bringing clarity and focus to research questions in clinical trials. Issue 1 (3rd January 2022) - Clark, Timothy Peter; Kahan, Brennan C; Phillips, Alan; White, Ian; Carpenter, James R
Abstract : Precise specification of the research question and associated treatment effect of interest is essential in clinical research, yet recent work shows that they are often incompletely specified. The ICH E9 (R1) Addendum on Estimands and Sensitivity Analysis in Clinical Trials introduces a framework that supports researchers in precisely and transparently specifying the treatment effect they aim to estimate in their clinical trial. In this paper, we present practical examples to demonstrate to all researchers involved in clinical trials how estimands can help them to specify the research question, lead to a better understanding of the treatment effect to be estimated and hence increase the probability of success of the trial.